Frequency and factors associated with adherence to and completion of combination antiretroviral therapy for prevention of mother to child transmission in western Kenya. Issue 1 (2nd January 2013) - Ayuo, Paul; Musick, Beverly; Liu, Hai; Braitstein, Paula; Nyandiko, Winstone; Otieno‐Nyunya, Boaz; Gardner, Adrian; Wools‐Kaloustian, Kara
Abstract : Introduction: The objective of this analysis was to identify points of disruption within the prevention of mother‐to‐child transmission (PMTCT) continuum from combination antiretroviral therapy (CART) initiation until delivery. Methods: To address this objective, the electronic medical records of all antiretroviral‐naïve adult pregnant women who were initiating CART for PMTCT between January 2006 and February 2009 within the Academic Model Providing Access To Healthcare (AMPATH), western Kenya, were reviewed. Outcomes of interest were clinician‐initiated change or stop in regimen, disengagement from programme (any, early, late) and self‐reported medication adherence. Disengagement was categorized as early disengagement (any interval of greater than 30 days between visits but returning to care prior to delivery) or late disengagement (no visit within 30 days prior to the date of delivery). The association between covariates and the outcomes of interest were assessed using bivariate (Kruskal‐Wallis test for continuous variables and the Chi‐square test for categorical variables) and multivariate logistic regression analysis. Results: A total of 4284 antiretroviral‐naïve pregnant women initiated CART between January 2006 and February 2009. The majority of women (89%) reported taking all of their medication at every visit. There were 18 (0.4%) deaths reported. Clinicians discontinued CART in 10 patients (0.7%) while 1367 (31.9%) women disengaged from care. Of those disengaging, 404 (29.6%) disengaged early and 963 (70.4%) late. In the multivariate model, the odds of disengagement decreased with increasing age (odds ratio [OR] 0.982; confidence interval [CI] 0.966–0.998) and increasing gestational age at CART initiation (OR 0.925; CI 0.909–0.941). Women receiving care at a district hospital (OR 0.794; CI 0.644–0.980) or tuberculosis medication (OR 0.457; CI 0.202–0.935) were less likely to disengage. The odds of disengagement were higher in married women (OR 1.277; CI 1.034–1.584). The odds of early disengagement decreased with increasing age at CART initiation (OR 0.902; CI 0.881–0.924). The odds of late disengagement decreased with increasing age at CART initiation (OR 0.936; CI 0.917–0.956). While they increased with higher CD4 counts at CART‐initiation (OR 1.001; CI 1.000–1001) and in married women (OR 1.297; CI 1.000–1.695) Conclusions: In a PMTCT programme embedded in an antiretroviral treatment programme with an active outreach department, the majority (67.4%) of women remained engaged and received uninterrupted prenatal CART.